Effect of the Similarity in Appearance of PTP Packaging between Original and Generic Drug Products on Safety Management for Medication - Ishima, Yu; Maruyama, Toru; Sugiyama, Yasuhiro; Sato, Hiroki; Okayama, Yoshiro; Watanabe, Hiroshi; Anraku, Makoto; Kadowaki, Daisuke; Watanabe, Yoko; Minagawa, Toshiya; Tsukioka, Ryota (Iryo Yakugaku (Japanese Journal of Pharmaceutical Health Care and Sciences), 2012)
In addition to promoting the reduction of medical costs, safety management for medication, such as the prevention of dispensing errors and dosing errors by patients, is also an important role of pharmacists in generic drug dispensing. While the similarity in appearance of press-through-package (PTP) drug products is known to have a significant influence on safety management for medication, none of the previous generic drug studies has focused on this issue. The objectives of this study were to evaluate the influence of the similarity in appearance of PTP packaging between original and generic drug products on safety management for medication, and to discuss preventative approaches. We first analyzed the risk of dispensing errors made by pharmacists working for community pharmacies and found that approximately 80% of responders had experienced near-miss episodes. Then, a similar analysis was conducted to determine the risk of dosing errors made by patients in their medication process and it was found that approximately 14% of patients had experienced episodes that could have led to misdosing due to packaging similarity. Furthermore, we also evaluated the similarity in PTP packaging of 1327 original and 1137 generic drug products and found that approximately 3% of all products (37 combinations) were considered to have a similar packaging appearance. These included high-risk drugs, such as digoxin and oral antidiabetics. We believe that an effective approach for reducing these risks is to promote information-sharing by listing those original and generic drug products that have similar PTP packaging appearance.